Fetal akinesia deformation sequence: Expanding the phenotypic spectrum. Issue 10 (8th July 2014) - Nayak, Shalini S.; Kadavigere, Rajagopal; Mathew, Mary; Kumar, Pratap; Hall, Judith G.; Girisha, Katta M.
<x xml:space="preserve">Abstract</x> We report on two unrelated fetuses born to nonconsanguineous couples with fetal akinesia deformation sequence (FADS). The fetuses shared facial features, micrognathia, fetal finger pads, bulbous digital tips, pterygia, clubfeet, ventriculomegaly, and cerebellar anomalies. Both had loss/absence of Purkinje cells in cerebellum. The first family had a similarly affected previous pregnancy suggesting an autosomal recessive inheritance. The second fetus, in addition to the findings in the first, had cleft palate and defective lobulation of lungs. These fetuses appear to have the Pena–Shokeir phenotype (PSP) or FADS. These two cases seem to define a newly recognizable subtype of FADS with bulbous digital tips, prominent digit pads and cerebellar anomalies, and highlight the phenotypic diversity of syndromes with multiple congenital contractures manifesting in utero. © 2014 Wiley Periodicals, Inc.